2016
DOI: 10.20411/pai.v1i2.115
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rates of Fluoroquinolone Resistance in Escherichia coli Blood and Urinary Isolates in Stem Cell Transplant and Hematologic Malignancy Populations

Abstract: Fluoroquinolone (FQ) antibiotics have been shown to reduce mortality and the number of febrile episodes when used as prophylaxis during neutropenia. Prior studies suggest that prophylaxis may result in increasing rates of FQ resistance. Fluoroquinolone non-susceptibility trends in Escherichia coli isolated from blood and urine cultures were evaluated over a 16-year period during which prophylaxis was initiated in patients with hematologic malignancies and stem cell transplants. Non-susceptibility rates increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A single large RCT, specifically assessing the high-risk hematology patient group, demonstrated fewer fevers with the use of levofloxacin prophylaxis, but without differences in infectious mortality or proven BSI [ 27 ]. The downstream consequences of widespread fluoroquinolone prophylaxis are now becoming evident with some centers reporting near-universal fluoroquinolone-resistant isolates from urine and blood of hematology patients [ 28 ]. Our low mortality highlights the safety of a fluoroquinolone prophylaxis-free approach in a setting where first line therapy is microbiologically inappropriate in 11.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A single large RCT, specifically assessing the high-risk hematology patient group, demonstrated fewer fevers with the use of levofloxacin prophylaxis, but without differences in infectious mortality or proven BSI [ 27 ]. The downstream consequences of widespread fluoroquinolone prophylaxis are now becoming evident with some centers reporting near-universal fluoroquinolone-resistant isolates from urine and blood of hematology patients [ 28 ]. Our low mortality highlights the safety of a fluoroquinolone prophylaxis-free approach in a setting where first line therapy is microbiologically inappropriate in 11.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent antibiotics recommended for the treatment of MDR-GNB 9nclude carbapenems (ie, meropenem), colistin, fosfomycin, tigecycline, aminoglycosides and antipseudomonal beta lactams (Table 1). 15,72…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the annual rate of fluoroquinolone non-susceptibility in E. coli increased across the study period 2000-2015 for both blood and urine isolates. 72 As mentioned before, polymyxins are identified as the last-resort treatment MDR Gram-negative bacteria, including E. coli. Regrettably, the spread of polymyxin resistance is on the rise amongst these microorganisms.…”
Section: Treatmentmentioning
confidence: 95%
“…In the 1980s and 1990s, gram-positive organisms caused the majority of infectious bacterial complications; however, in the past decade gram-negative infections have become the predominant infections in many centers [4446]. Along with this reversal of ratio between gram-positive and gram-negatives, there has been a dramatic increase in multi-drug-resistant bacteria [47•, 48•, 49•, 50•].…”
Section: Potential Risks Of Antibiotic Prophylaxismentioning
confidence: 99%